Translating sickle cell guidelines into practice for primary care providers with Project ECHO. Issue 1 (1st January 2016) - Shook, Lisa M.; Farrell, Christina B.; Kalinyak, Karen A.; Nelson, Stephen C.; Hardesty, Brandon M.; Rampersad, Angeli G.; Saving, Kay L.; Whitten-Shurney, Wanda J.; Panepinto, Julie A.; Ware, Russell E.; Crosby, Lori E.
Abstract : Background: Approximately 100, 000 persons with sickle cell disease (SCD) live in the United States, including 15, 000 in the Midwest. Unfortunately, many patients experience poor health outcomes due to limited access to primary care providers (PCPs) who are prepared to deliver evidence-based SCD care. Sickle Treatment and Outcomes Research in the Midwest (STORM) is a regional network established to improve care and outcomes for individuals with SCD living in Indiana, Illinois, Michigan, Minnesota, Ohio, and Wisconsin. Methods: STORM investigators hypothesized that Project ECHO ® methodology could be replicated to create a low-cost, high-impact intervention to train PCPs in evidence-based care for pediatric and young adult patients with SCD in the Midwest, called STORM TeleECHO. This approach utilizes video technology for monthly telementoring clinics consisting of didactic and case-based presentations focused on the National Heart, Lung and Blood Institute (NHLBI) evidence-based guidelines for SCD. Results: Network leads in each of the STORM states assisted with developing the curriculum and are recruiting providers for monthly clinics. To assess STORM TeleECHO feasibility and acceptability, monthly attendance and satisfaction data are collected. Changes in self-reported knowledge, comfort, and practice patterns will be compared with pre-participation, and 6 and 12 months after participation. Conclusions: STORM TeleECHO has the potential to increase implementation of the NHLBI evidence-based guidelines, especially increased use of hydroxyurea, resulting in improvements in the quality of care and outcomes for children and young adults with SCD. This model could be replicated in other pediatric chronic illness conditions to improve PCP knowledge and confidence in delivering evidence-based care.